Biology and Medicine-Related Examples for General Chemistry Lectures - Elizabeth Taylor; Catherine L. Drennan (Association of American Medical Colleges, 2010)
Abstract This resource features 15 brief in-class examples for general chemistry lectures that relate chemical principles to inspiring topics in biology and medicine. Running between 2 to 5 minutes each, the examples are short enough to incorporate into lectures without the need to remove course content. Each example includes background information for the instructor and PowerPoint slides that can be used directly in the classroom. Most examples include an in-class question within the PowerPoint slides for use with or without classroom response devices. The examples are ideal for general chemistry instructors looking to convey the relevance of chemistry and to promote interdisciplinary thinking and the application of chemical principles to human health and medicine in their lectures. The resource includes an instructor's guide, a 97-slide PowerPoint presentation with approximately five to 10 slides per example, and a 27-page file with instructor background information for each of the biology and medicine-related examples. As freshman chemistry instructors, we looked to integrate inspiring examples into our curriculum and encourage interdisciplinary thinking, but did not have the flexibility to remove any of the chemistry content from our course to make room for new units. By creating short examples that relate chemical principles to biology and medicine, we are able to help student see the relevance of chemical principles and promote problem solving across disciplines.